Web data mining : - Liu, Bing (Springer, 2007)
This book offers a rich blend of theory and practice, addressing seminal research ideas, as well as examining the technology from a practical point of view. The content provides useful information and knowledge from the Web hyperlink structure, page contents, and usage data. Although Web mining uses many conventional data mining techniques, it is not purely an application of traditional data mining due to the semistructured and unstructured nature of the Web data and its heterogeneity. It has also developed many of its own algorithms and techniques